2009
DOI: 10.1016/j.regsciurbeco.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake risk and housing prices in Japan: Evidence before and after massive earthquakes

Abstract: The hedonic pricing approach is used to examine whether homeowners and/or renters alter their subjective assessments of earthquake risks after massive earthquakes. Using nation-wide household panel data coupled with earthquake hazard information and records of observed earthquakes, we find that there are some modifications of individuals' assessments of earthquake risk in both cases. We have carefully taken into consideration the bias stemming from the use of objective risk variables as a proxy for individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 18 publications
6
64
1
2
Order By: Relevance
“…An important caveat, also highlighted elsewhere 24 , is that not all lower-income households living in hazard-exposed areas are necessarily 'trapped' there; some households do want to live in these areas, for diverse reasons. Although many economic studies have shown price discounts for properties in hazard-exposed areas [25][26][27][28][29][30][31] , we show that this is linked to people's stated motivations and to movement toward less-exposed areas by higher-income households. Finally, although many studies have observed that hazard-exposed areas tend to be occupied by lower-income households [32][33][34] , we show the origination of this pattern as a result of new knowledge of the risk and an abundant supply of aid housing provided in hazard-exposed areas.…”
Section: Discussionmentioning
confidence: 52%
“…An important caveat, also highlighted elsewhere 24 , is that not all lower-income households living in hazard-exposed areas are necessarily 'trapped' there; some households do want to live in these areas, for diverse reasons. Although many economic studies have shown price discounts for properties in hazard-exposed areas [25][26][27][28][29][30][31] , we show that this is linked to people's stated motivations and to movement toward less-exposed areas by higher-income households. Finally, although many studies have observed that hazard-exposed areas tend to be occupied by lower-income households [32][33][34] , we show the origination of this pattern as a result of new knowledge of the risk and an abundant supply of aid housing provided in hazard-exposed areas.…”
Section: Discussionmentioning
confidence: 52%
“…The majority of the literature uses local housing transaction data as well as repeated sales data to single out the effects of risks originating from hazardous waste sites (Kohlhase 1991, Kiel 1995, Kiel and McClain 1995, Gayer and Viscusi 2002, Greenstone and Gallagher 2008. Naoi, Seko and Sumita (2009) analyzed rents and owner-provided value for houses in a household panel survey to show that risk perception toward earthquakes experienced upward revision after major earthquakes. Other studies analyzing the impact of spent nuclear waste used their transportation route (rail track) and proximity to assess their impact on local housing prices Jenkins-Smith 2001, Gawande et al 2013).…”
Section: Literaturementioning
confidence: 99%
“…10 denotes their endowed income, which is the same for everybody. Earthquake insurance contracts specify the premium and the indemnity paid in case of an earthquake , .…”
Section: The Modelmentioning
confidence: 99%
“…The authors are very grateful for the referee on this point. 10 Ehrlich and Becker (1972) examine two alternatives to market insurance: self-insurance -a reduction in the size of a loss -and self-protection -a reduction in the probability of a loss. They show that market insurance and self-insurance are substitutes.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation